A selective and easily recyclable dimer based on a calix[4]pyrrole derivative for the removal of mercury(ii) from water. Issue 6 (16th January 2020) - Danil de Namor, Angela F.; Alharthi, Salman; Howlin, Brendan; Al Hakawati, Nawal
Abstract : A recyclable mercury(ii ) selective dimer based on a calix[4]pyrrole derivative has been synthesised and characterised by mass and FT-IR spectrometry, Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX). Abstract : A recyclable mercury(ii ) selective dimer based on a calix[4]pyrrole derivative has been synthesised and characterised by mass and FT-IR spectrometry, Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX). Information regarding the ability of the dimer to interact with metal cations was obtained from FTIR and SEM-EDX analyses. A striking feature of micrographs of the loaded dimer is the change of morphology with the cation. Based on these results, optimal conditions for removing cations from water were assessed under different experimental conditions. Results obtained demonstrate that the removal process is fast. Capacity values and selectivity factors show that the dimer is selective for Hg(ii ) in single and multiple component metal solutions relative to other cations. Single-ion transfer Gibbs energies from water to a solvent containing common functionalities to those of the dimer were used to assess the counter-ion effect on the removal process. Agreement is found between these data and energy calculations derived from molecular simulation studies. Studies on polluted water in the presence of normal water components in addition to toxic metal cations are reported. Further experimental work on wastewater from the mining industry is in progress.